The association between changes in proteinuria and the risk of cerebral infarction in the Korean population. (October 2022) - Park, Sung Keun; Jung, Ju Young; Kim, Min-Ho; Oh, Chang-Mo; Ha, Eunhee; Shin, Soon Su; Lee, Hyo Choon; Hwang, Woo Yeon; Ryoo, Jae-Hong
Abstract: Background: Proteinuria is a risk factor for cerebral infarction. It is known that proteinuria can change over time. However, published data is scarce for the association between changes in proteinuria and the risk of cerebral infarction. Method: Study participants were 276, 861 Koreans who were assessed for urine dipstick proteinuria both in 2003–2004 and 2007–2008. They were categorized into four groups by changes in proteinuria over 4 years (negative: negative → negative, resolved: proteinuria ≥ 1+ → negative, incident: negative → proteinuria ≥ 1+, persistent: proteinuria ≥ 1+ → proteinuria ≥ 1 + ). We used multivariate adjusted Cox-proportional hazard model in calculating the adjusted hazard ratios (HR) and 95% confidence interval (CI) for cerebral infarction until 2013 according to changes in proteinuria. Result: Adjusted HR and 95% CI for cerebral infarction significantly increased in order of persistent, incident, and resolved proteinuria, compared with negative proteinuria (negative: reference, resolved: 1.166 [1.009–1.347], incident: 1.345 [1.188–1.522], and persistent: 1.443 [1.089–1.912]). In gender subgroup analysis, men showed the more clear association between changes in proteinuria and the risk of cerebral infarction (negative: reference, resolved: 1.284 [1.057–1.560], incident: 1.351 [1.149–1.589], and persistent: 1.428 [1.014–2.012]). Conclusion: All types of proteinuria changes were associated with the increased risk of cerebral infarction, even in participants with once manifested but vanishing proteinuria.